2011
DOI: 10.1038/onc.2011.399
|View full text |Cite
|
Sign up to set email alerts
|

The oncogenic phosphatase PPM1D confers cisplatin resistance in ovarian carcinoma cells by attenuating checkpoint kinase 1 and p53 activation

Abstract: Cisplatin (CDDP: cis-diamminedichloroplatinum) resistance is a major hurdle in the treatment of human ovarian cancer (OVCA). A better understanding of the mechanisms of CDDP resistance can greatly improve therapeutic outcome for patients. A determinant of CDDP sensitivity in OVCA, p53, is activated by checkpoint kinase 1 (Chk1) in response to DNA damage. Although the oncogenic phosphatase protein phosphatase magnesium-dependent 1 (PPM1D) can deactivate both p53 and Chk1 through sitespecific dephosphorylation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 45 publications
5
57
0
Order By: Relevance
“…1H) (16); and multidrug resistant OVCAR-3 ovarian cancer cells, which are resistant to 5 μM ICI (Fig. 1I) and to paclitaxel, cisplatin, and other anticancer drugs (17,18). BHPI blocked proliferation in all 15 ERα + cell lines and at 10 μM had no effect on proliferation in all 12 ERα − cell lines tested (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1H) (16); and multidrug resistant OVCAR-3 ovarian cancer cells, which are resistant to 5 μM ICI (Fig. 1I) and to paclitaxel, cisplatin, and other anticancer drugs (17,18). BHPI blocked proliferation in all 15 ERα + cell lines and at 10 μM had no effect on proliferation in all 12 ERα − cell lines tested (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Absorbance at 490 nm was determined by a Bio-Rad X-Mark microplate analyzer. Apoptosis was assessed based on stereotypic morphological changes, including chromatin condensation, nuclear fragmentation cytoplasmic shrinkage, and the formation of apoptotic bodies (with nuclear fragments) as assessed in previous studies (11,27,28). At least 400 cells/treatment group were counted, and the quantification process was blinded to avoid experiment bias.…”
Section: Mts Assay and Hoechst 33258mentioning
confidence: 99%
“…To test this hypothesis, we utilized a series of biophysical and biochemical techniques to understand the response of ovarian cancer cells to a soft matrix similar to adipose tissue and a stiff matrix similar to tumor tissue (Samani et al, 2007;Tse and Engler, 2010), using both the more-metastatic SKOV-3 and the lessmetastatic OVCAR-3 human cell lines (Slack-Davis et al, 2009), both of which harbor either mutated or deleted p53, indicative of high-grade serous ovarian carcinomas (Ali et al, 2012;Domcke et al, 2013;Salani et al, 2008). We found that OCCs show increased adhesion on soft microenvironments.…”
Section: Introductionmentioning
confidence: 99%